Konsep Surga dan Neraka dalam Budaya Nias serta Implikasinya bagi Pembelajaran Pendidikan Agama Katolik - Sergius Lay; Junita Hulu; Selvianti Dakhi; Yasman Handayani Lase; Natalia Harefa; Atanasius Zai; Antonius P Sipahutar (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This research investigates the concepts of heaven and hell within Nias culture and compares them with Catholic Church teachings, exploring their implications for Catholic Religious Education (PAK). Driven by the disparity in eschatological understanding between local culture and Catholic doctrine, and the crucial role of inculturation in faith life, a qualitative approach employing literature review was adopted. Data sources included Church documents, books, and relevant scholarly journals. Findings reveal that Nias culture perceives post-mortem existence not as a dualistic heaven or hell, but as a continuation in the spirit world, influenced by social status and adherence to tradition. In contrast, Catholic teachings define heaven and hell as outcomes of humanity's relationship with God. The inculturation process highlights a dialogue between cultural values and Christian faith, demonstrating that integrating local cultural values into PAK can enhance students' faith experience, making learning more relevant and transformative within their contexts.